The reflective factors of students’ determination for effective learning in higher education - Yundayani, Audi; Alghadari, Fiki (S&Co Publishing, 2025)
Promoting self-determination was identified as facilitating access to effective learning in higher education contexts. However, amidst the competitive educational climate and various contemporary educational issues, there remained a gap in understanding the factors influencing its implementation. This study explored the factors that reflected students' self-determination for effective learning. This quantitative study involved two hundred and eighty-five participants from private universities. Data were collected using a questionnaire containing twenty-three statement items to measure students' determination in their learning, and then the data were analyzed using exploratory and confirmatory factor analysis. The study revealed six factors of student determination for effective learning. They were learning control and flexibility, learning strategy development, academic ability and engagement, academic progress and evaluation management, perception of the academic environment, and collaboration and social engagement. These factors need to be considered in developing strategies and educational interventions that are truly efficient, as in a teaching scenario, to facilitate students' self-determination performance and promote academic success and student well-being.